A case study of two South Korean middle school EFL teachers' practices: instructional stances and use of classroom materials. Issue 1 (3rd April 2021) - Han, Soyoung; Liang, Di; Haneda, Mari
ABSTRACT: This case study uses a sociocultural theoretical perspective to examine how two Korean middle-school EFL teachers nurtured participatory affordances for their students through classroom discourse. We conducted a triangulated analysis of video-recorded classroom discourse, observational notes and teacher interviews. Our findings show how the teachers' instructional stances, namely orientations to teaching, were linked to their use of materials and their interactional practices. While Ms. Yoon's instructional stance was undergirded by a focus on grammatical accuracy, Ms. Jin's stance was student-centred, driven by her desire to make English-language learning meaningful. The teachers' instructional stances, in turn, fundamentally shaped their discursive strategies, their uses of L2 materials, and the learning opportunities these produced for students. Using decontextualised examples, Ms. Yoon relied on a rapid-paced Initiation-Response-Evaluation (IRE) pattern, positioning students as knowledge-receivers. By contrast, Ms. Jin enacted more dialogic interaction using meaningful intertextual links and playful talk, which resulted in students' active participation, evidenced by their initiation of topics and extended answers. Our study contributes to nascent classroom-based research on L2 material use by suggesting two additional areas for research: the link between teacher instructional stance and L2 material use and intertextual links as a mediational tool for learning.